Leadership and Employee Productivity at The Galatta Lestarindo Fertilizer Company - Nusfiyah, Khuzrotun; Al Maghfuri, Rahmah Salsabila (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of this study was to determine the positive and significant influence of leadership on employee work productivity at the fertilizer company Galatta Lestarindo. The collection method is through interviews and submission of questions by means of a questionnaire involving 25 respondents. Analysis tools in the form of correlation and regression as well as data processing with SPSS software. The results showed a correlation coefficient of 0.714, an R Square value of 0.510 meaning that 51% of changes that occur in productivity can be explained by leadership. Correlation value of 0.714 has a positive and significant relationship between leadership and employee work productivity at the fertilizer company Galatta Lestarindo